PERILAKU BERPACARAN SISWA SMA NEGERI KOTA BUKITTINGGI - Sucita Qalbina; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Dating behavior among adolescence has become a very common phenomenon and is easily found in society. Dating behavior according to sociological perspective is included in deviant behavior because dating is part of promiscuity. Behavior can be influenced by several factors both from within (self) and from outside (environment), which lifestyle becomes one of it. This study aims to determine: (1) the dating behavior of Public High School students in Bukittinggi, (2) the factors that influence their dating behavior. The method used in this study is correlational quantitative and simple linear regression. The population in this study is the students who are dating, attended public high school in Bukittinggi, and domiciled in Bukittinggi as well. The sampling technique this study used is quota sampling with the sample of 20 students from each high schools so a total sample of 100 students is found. The results showed that the dating behavior of the students is still within reasonable limits with a low score of 220. The influencing factors included in this study are parents' socio-economic factors, student's relationship with their family members and student's obedience in worship (religiousness), with the highest influencing factor is the negative relationship with their male parent. While the influence of hedonism lifestyle is found to have an influence as much as 21.6% while the rest 78.4% is influenced by other factors. Keywords: Dating behavior, Influencing factors, Lifestyle